Manajemen Strateegi Dalam Mengatasi Kekurangan Guru Metode Ummi Berbasis Bahasa Ibu Di Mi Al Ishlah Bobos Cirebon - Luthfanie, Dhika; Ali, Moh.; Cahyani, Dewi (JURNAL MANAJEMEN PENDIDIKAN, 2026)
STRATEGIC MANAGEMENT IN OVERCOMING THE SHORTAGE OF UMMI METHOD TEACHERS BASED ON MOTHER-TONGUE APPROACH AT MI AL ISHLAH BOBOS CIREBON This study aims to describe the managerial strategies implemented by MI Al-Ishlah Bobos Cirebon, in overcoming the shortage of human resources (HR) of teachers in the implementation of the mother tongue-based Ummi Method at MI Al-Ishlah Bobos Cirebon. The results of our observations and data collection on the implementation of the mother tongue-based Ummi method show various phenomena that occur. Among these phenomena, we take one of the phenomena, namely the limited number of teachers certified by the Ummi Method and the low ability of some teachers in implementing the principles of talaqqi and tartil, resulting in less than optimal learning of the Ummi method at MI Al-Ishlah Bobos Cirebon. The Ummi method was chosen because it emphasizes a mother tongue approach, direct reading, repetition, and affection, which are believed to improve students' reading skills. This study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results showed that the institution implemented several managerial strategies, namely: (1) mentor-based internal training; (2) mentoring by the Ummi Foundation in the Cirebon region; (3) recruitment of local mother tongue teachers; (4) integration of mother tongue in Qur'an learning; and (5) routine coaching. These strategies have proven effective in improving teacher competence and the quality of students' Qur'an recitation. These findings indicate that the use of mother tongue can be a contextual solution in managing Qur'an learning in Islamic madrasas, especially when faced with limited human resources.